Draft Annual Plan 1999-2000 Volume I (Part-I) Government of Uttar Pradesh - Planning Commission (Planning Commission, 1999)
Agriculture, as we all know, is the most dominant sector of state’s economy, with its highest and near static share of about 42% in state income for the past several years and a still larger share of about 73% of state’s work-force hanging on to it without any signs of some significant abatement. Apart from Highlighting the significance of this sector for state’s economy for the time being, this is also an evidence, at the same time, of near total lack of diversification in the economy.
Government of Uttar Pradesh, State Planning Commission